Membaca Simbol pada Lukisan Pertempuran Antara Sultan Agung dan Jan Pieterszoon Coen (1974) Karya S. Sudjojono - Wulandari, Anak Agung Ayu (Bina Nusantara University, 2015)
Sudjojono has produced hundreds of artworks, one of them is the painting of ?The Battle between Sultan Agung and Jan Pieterszoon Coen?. Sizing 3 x 10 m, not only this painting is significant in size, it also shows Sudjojono?s in-depth study from aesthetic and historical side. The painting consists of 3 panels depicting Sultan Agung?s meeting with his royals, the battle scene between Mataram and Dutch troops, and the last panel depicting the meeting between JP Coen and Kyai Rangga. Some of the message conveyed by the painter is that the painting was 70% made of historical facts and did not come from the painter imagination only, better to be in peace than war and revenge and the last message is that western and eastern people are actually equal, and as eastern people should not need to have low self-esteem. Besides those messages there are still many symbols and signs that have in-depth meaning which will be studied and examined thoroughly such as figures involved in the battle, location of battle, clothing, etc.